1990
DOI: 10.1037/0882-7974.5.3.429
|View full text |Cite
|
Sign up to set email alerts
|

Social support, life events, and stress as modifiers of adjustment to bereavement by older adults.

Abstract: As part of a larger panel study interviews were obtained from 3 samples of older adults: 45 persons who had recently lost a spouse, 40 who had lost a parent or child, and 45 who were not bereaved. Assessments were conducted before and after the deaths. In the widowed sample, health remained quite stable, but depression increased sharply, then remained elevated. Changes were minimal in the sample who had lost a parent or child and in the nonbereaved sample. Multiple regression procedures were used to identify f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
90
2
2

Year Published

1999
1999
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 152 publications
(110 citation statements)
references
References 42 publications
15
90
2
2
Order By: Relevance
“…All three studies assessing health and/or physical limitations found significant relationships between poor health and onset of BRD (Clayton, 1975;McHorney & Mor, 1988;. Five of six studies measuring social support found an inverse relationship between social supports and BRD (Clayton, 1975;Dimond et al 1987 ;Norris & Murrell, 1990;Nuss & Zubenko, 1992).…”
Section: Concurrent Validatorsmentioning
confidence: 99%
See 2 more Smart Citations
“…All three studies assessing health and/or physical limitations found significant relationships between poor health and onset of BRD (Clayton, 1975;McHorney & Mor, 1988;. Five of six studies measuring social support found an inverse relationship between social supports and BRD (Clayton, 1975;Dimond et al 1987 ;Norris & Murrell, 1990;Nuss & Zubenko, 1992).…”
Section: Concurrent Validatorsmentioning
confidence: 99%
“…None of these studies compared BRD to SMD. One of the studies compared bereaved to matched non-bereaved individuals (Norris & Murrell, 1990), three compared bereaved persons with BRD to those without depression (Clayton, 1975;McHorney & Mor, 1988;Zisook & Shuchter, 1991 b) and three examined bereaved populations without comparison groups (Dimond et al 1987 ;Nuss & Zubenko, 1992). All three studies assessing health and/or physical limitations found significant relationships between poor health and onset of BRD (Clayton, 1975;McHorney & Mor, 1988;.…”
Section: Concurrent Validatorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Again, this finding is similar to those of Meuser (2002, 2005) who found a similar relationship between AG and social support. This result is also consistent with the bereavement literature which has reliably demonstrated that support from family and friends is one of the strongest predictors of bereavement outcomes including depression and grief symptomatology (Sanders, 1993;Stroebe, Stroebe, Abakoumkin, & Schut, 1996;Norris & Murrell, 1990). …”
Section: Study Question One: Is Ag Related To Caregiver Burden and Itsupporting
confidence: 80%
“…Just as the aging process is often associated with the experience of desirable life events (Norris & Murrell, 1990) such as grandparenthood and retirement, it is also associated with the experience of less desirable life events, such as the loss of a loved one (Hansson, Hayslip & Stroebe, 2007). Death rate statistics show that older adults are not only experiencing the greatest number of deaths within their age group compared to their younger counterparts, but also have the opportunity to experience the widest variety of bereavements in terms of type of relationship to the deceased (U.S. Department of Health and Human Services, 2010).…”
Section: Overview and Aimmentioning
confidence: 99%